2018
DOI: 10.12688/f1000research.15995.1
|View full text |Cite
|
Sign up to set email alerts
|

Virologic failure and HIV drug resistance on simplified, dolutegravir-based maintenance therapy: Systematic review and meta-analysis

Abstract: Background: Dolutegravir-containing maintenance therapy is a promising simplification strategy for virologically suppressed HIV-infected individuals. However, most of the available data to inform this strategy come from small, uncontrolled studies. We estimated the proportion of HIV-infected patients experiencing virological failure (VF) and developing drug resistance on dolutegravir (DTG)-based maintenance therapy. Methods: We searched Medline, Embase, Cochrane Central, Web of Science, and conference abstract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 32 publications
3
10
0
2
Order By: Relevance
“…In addition to the clinical value of DTG forming part of three-drug regimens, several clinical trials and meta-analyses have shown that DTG-containing two-drug ART regimens, particularly the combinations of DTG with lamivudine (3TC) or rilpivirine (RPV), have similar efficacy in achieving and maintaining virological suppression (VS) in PLHIV. This is achieved whilst reducing the number of ART agents and potential risk of drug-drug interactions owing to the simplified regimen compared with triple ART regimens [14,[19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the clinical value of DTG forming part of three-drug regimens, several clinical trials and meta-analyses have shown that DTG-containing two-drug ART regimens, particularly the combinations of DTG with lamivudine (3TC) or rilpivirine (RPV), have similar efficacy in achieving and maintaining virological suppression (VS) in PLHIV. This is achieved whilst reducing the number of ART agents and potential risk of drug-drug interactions owing to the simplified regimen compared with triple ART regimens [14,[19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of this study is the fact that the MARISA model does not take into account resistance to DTG and uses a simplified representation of NRTI resistance. In the context of the introduction of DTG-based ART, modeling of NRTI resistance is particularly relevant as individuals starting on DTG as a functional monotherapy due to resistance to both NRTI backbones—TDF and 3TC—experience higher risk of treatment failure [ 27 ]. As they are considerably less frequently transmitted [ 28 ] and revert back quickly [ 29 , 30 ], NRTI resistances might primarily be an issue for ART-experienced individuals and more specifically, in patients failing NNRTI-based regimens, who often exhibit high levels of NRTI resistance [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this study is the fact that the MARISA model does not take into account resistances to neither NRTI nor DTG. In the context of the introduction of DTG-based ART, modelling of NRTI resistance is particularly relevant as individuals starting on DTG as a functional monotherapy due to resistance to both NRTI backbones - tenofovir and lamivudine - experience higher risk of treatment failure [25]. As they are considerably less frequently transmitted] [26] and revert back quickly [27, 28], NRTI resistances might primarily be an issue for ART-experienced individuals and more specifically, in patients failing NNRTI-based regimens, who often exhibit high levels of NRTI resistance [29].…”
Section: Discussionmentioning
confidence: 99%